PERAN PENGAKUAN DOSA SEBAGAI SARANA KONSELING PASTORAL BAGI NARAPIDANA BERDASARKAN MAZMUR 51:1-21 - Manginsihi, Ester Ribka Johana; Brek, Yohan (PT. Giat Konseling Nusantara, 2024)
The purpose of this literature research is to find out the role of confession as a means of pastoral counseling for prisoners based on Psalm 51:1-21. Researchers used literature research along with historical critical studies on texts. Based on the results of the research, Psalm 51:1-21 is a form of self-expression for a person or even a group of people who are aware, admit, and regret their sins and in this case Psalm 51:1-21 can be a means of pastoral counseling in bringing prisoners to living in confession, awareness, and regret for sins that have been committed so that holistic healing slowly begins to be experienced both physically, mentally, socially, psychologically, and spiritually. And also based on the results of the discussion of this research there is a function of pastoral counseling including the function of reconciling, sustaining, strengthening and empowering.